Industrial training report: Malaysian Institute of Accountants (MIA) / Mohammad Atif Mohammad - Mohammad, Mohammad Atif (Universiti Teknologi MARA, Perlis, 2024)
This executive brief summarises the internship experience at Malaysian Institute of Accountants (MIA) and highlights the important findings and suggestions. The internship was in the Membership department and lasted from September 1st, 2023, to February 9th, 2024. Verifying member contributions, aiding the members with necessary needs, and using the data provided to guide and update them as an accountant or practitioner. The intern benefited from intrinsic advantages such as experiences, knowledge, and skill development, as well as an extrinsic benefit of a RM700 monthly allowance with the availability of over time. According to the SWOT analysis, under the Accountants Act of 1967, the Malaysian Institute of Accountants (MIA) is the only statutory entity responsible for regulating and developing the accounting profession in Malaysia, as well as accrediting and certifying chartered accountants. The institute has drawbacks including member non-compliance despite strengths like its exclusive statutory position. In order to boost revenue, MIA takes advantage of possibilities associated with budget releases by providing coaching sessions and seminars. However, "Bogus Accountants" who take a less strict route and create liability issues are the main threat. Increased outreach, sanctions for non-compliance, proactive steps against fraudulent accountants, and motivational speeches to keep students interested in accountancy are among the recommendations.